Dust grain in streaming ions with temperature variation - S. Sundar (Physical Sciences and Technology, 2019)
This work presents improved numerical observations to demonstrate influence of the ion-to-electron temperature ratio on the dust grain in streaming non-Maxwellian ions for a range of ion speeds. Increase in electron-to-ion temperature ratio influences the ion-grain dynamics substantially and manifests itself as an enhancement in the wake amplitude. The interplay of streaming ion speed with temperature and their synergistic impact on the wake potential and density of the grain is discussed in detail. Physical properties like peak potential and peak position and its dependence on temperature, collision, and streaming speeds is presented. A comparison of the results obtained using 3D-6V particle-in-cell simulation with that of the linear response approach is delineated systematically. At lower temperature, peak potential and peak position exhibit monotonic increase with collision. However, at higher temperature the behavior becomes non-monotonic and initially exhibits an increase in the peak potential with collision and then a decreasing trend. For moderate streaming speeds at lower temperatures, splitting of ion focus behind grain is observed from the density contours as well as three-dimensional potential plots. Our results are reasonably consistent with that of the earlier results reported using Linear Response formalism, nevertheless, in certain regimes it endows us with richer physics.